BMP4 promotes metastasis of hepatocellular carcinoma by an induction of epithelial–mesenchymal transition via upregulating ID2. (1st April 2017) - Zeng, Shan; Zhang, Yan; Ma, Junli; Deng, Ganlu; Qu, Yanlin; Guo, Cao; Han, Ying; Yin, Ling; Cai, Changjing; Li, Yiyi; Wang, Guqi; Bonkovsky, Herbert L.; et al.
Abstract: The role of bone morphogenetic protein 4 (BMP4), a crucial epithelial–mesenchymal transition (EMT) mediator, in the progression of hepatocellular carcinoma (HCC) patients heretofore has not been elucidated. The present study analyzed BMP4 expression in tumors and paired non-tumorous liver tissue and its correlation with clinicopathological characteristics from two independent cohorts consisting of 420 HCC patients. Functional analysis of BMP4 was performed in Bel-7402 and HCCLM3 HCC cells, and in a murine HCC model. The downstream targets of BMP4 in HCC were screened and confirmed. The results indicated that BMP4 expression was significantly increased in HCC tissue and highly metastatic HCC cells. BMP4 expression was correlated with vein invasion, overall survival and recurrence-free survival of HCC. BMP4 promoted HCC EMT and metastasis in vitro, and consistently in vivo . BMP4 knockdown blocked EMT and tumor metastasis in nude mice. ID2 was up-regulated by recombinant human BMP4, resulting in HCC EMT. Knockdown of ID2 blocked BMP4-induced EMT. In conclusion, BMP4 promotes invasion and metastasis of HCC by an induction of EMT via up-regulating ID2. BMP4 may be a valuable prognostic factor and potential therapeutic target for HCC therapy.